Is microbiota a factor in the mechanism of glaucoma development? - O. I. Orenburkina; A. E. Babushkin; S. M. Shamsutdinov (Российский офтальмологический журнал, 2024)
Nowadays, glaucoma is viewed as a multifactorial neurodegenerative condition that involves many factors affecting different cell types in a human body. As is known, increased intraocular pressure (IOP) is not the only threatening factor of ganglion cell apoptosis and glaucomatous optic neuropathy development; IOP can be associated with other factors, such as vascular, metabolic, neurotrophic, immune, inflammatory, etc. However, the treatment of glaucoma remains largely symptomatic, aimed almost exclusively at reducing IOP. Microbiotic dysbiosis is a newly developing research direction of the glaucomatous progress, showing that this mechanism may turn out to be an important factor of glaucoma development. There are reasons to believe that treatment strategies aimed at microbiota damage correction may contribute to a better efficiency of glaucoma management.